Moving Away and Reaching Out: Young Adults' Relational Maintenance and Psychosocial Well-Being During the Transition to College. Issue 2 (2nd April 2016) - Burke, Tricia J.; Ruppel, Erin K.; Dinsmore, Dana R.
ABSTRACT: In this study, we extended the research on students' stress and psychosocial well-being during the transition to college to consider the potential moderating effect of their communication of relational maintenance with a parent. We found that as students' ( N = 155) daily stress increased, their daily loneliness and depression increased, and their daily happiness decreased. Moreover, we identified students' daily communication of openness and assurances with a parent as moderators of the association between their daily stress and daily loneliness. These results suggest that students' communication with a parent is a salient factor in their well-being during the transition to college.